ANALISIS STRUKTUR DAN NILAI MORAL DALAM NOVEL HANDEULEUM NA HATE BEUREUM KARYA CHYE RETTY ISNENDES - Denti Yolanda; Opah Ropiah (Prodi Pendidikan Bahasa dan Sastra Daerah, 2022)
This study aims to describe the structure and moral values ​​contained in the novel Handeuleum na Haté Beuruem by Chye Retty Isnendes. The method used in this research is descriptive analysis using data collection techniques, literature review and data analysis. Based on the analysis of the structure of the story, the theme of this novel is about love. The flow used is the forward flow. There are 11 characters. There are 14 place settings in this novel, the background of the situation is sad and disappointed. The point of view uses a third-person omniscient point of view. The language style used is hyperbole, personification style, pleonasm language style, babasan language style and proverb, and foreign language style. Based on the results of the analysis of human moral values ​​to God, namely believing in destiny and God's power, human morals towards themselves are trustworthy, smart, wise, self-aware, busy, selfish, and suudzon, humans towards other humans understand others, respect others, caring, sociable, wise, flirtatious, indifferent, arrogant, envious, curious, human morals towards time, namely making time effective, human morals to get inner and outer happiness, namely the footing in satisfying desires